Growing importance of women in the German labor market - Karl Brenke (DIW Economic Bulletin, 2014)
An increasing share of the working-age population is active in the German labor market. In particular, the number of women participating in the labor force has grown. The more highly qualified they are, the greater their participation in the labor market - and the level of qualification among women has increased considerably, now approaching that of men. Regardless of their qualifications, women's willingness to participate in the labor market has risen appreciably in all age groups. Among men, this was largely only the case in older age groups. The number of female employees has increased almost constantly and is hitting record highs. For men, the progression was more variable and the number of individuals employed since the middle of the last decade is only slightly higher than in the early 1990s, despite notable increases. Nevertheless, there are still fewer women overall: in 2013, women made up 46 percent of the whole labor force; their share of total work volume is even smaller at 40 percent. This is mainly due to the fact that almost half of women in Germany work part-time. This strong increase in female participation in the workforce is largely due to sectoral changes. Employment in Germany has increased considerably, particularly in sectors where comparatively more women work. Conversely, in sectors such as manufacturing, which is generally a predominantly male field, the development of jobs has been less favorable.
Keywords: J16; J21; J22; 330; women in the labor market; labor force participation; employment